Lower extremity muscle hypertrophy in response to resistance training in older adults: Systematic review, meta-analysis, and meta-regression of randomized controlled trials - Davi Alves de Santana; Pedro Godoi Scolfaro; Emanuele Marzetti; Cláudia Regina Cavaglieri (Experimental Gerontology)
Objectives: This study aimed to investigate the effects of resistance training (RT) on knee extensor muscle hypertrophy in adults 65 years and older. Methods: A systematic search was carried out in PubMed, Embase, and Scopus to review randomized controlled trials that assessed the effects of supervised RT on 1) muscle size, 2) fiber area, and 3) leg lean mass (LLM). Random-effects meta-analyses of standardized mean difference (SMD) and raw mean difference (RMD) for LLM were calculated. We performed a meta-regression to examine the interference of age, training volume, and duration on the results related to hypertrophy at muscle and fiber levels. Results: Thirty-two studies were included in the review, and 28 were meta-analyzed. The meta-analysis found a significant effect of RT on muscle size (SMD = 0.34; 95 % CI: 0.16–0.52; p < 0.001) and fiber area (SMD = 0.54; 95 % CI: 0.24–0.84; p < 0.001), but not on LLM (RMD = 0.22; 95 % CI: −0.22-0.66 p = 0.321). A subanalysis of studies that assessed quadriceps femoris size (excluding isolated quadriceps femoris muscles from the analysis) also revealed a significant effect of RT (95 % CI: 0.20–0.69; p < 0.001). Regression analysis indicated a significant influence of intervention duration on type II fiber area (p = 0.034), while no significant influence was detected for weekly sets or age for any outcome measure. Conclusions: RT promotes muscle hypertrophy in older adults at both whole-muscle and fiber levels, with training duration potentially influencing the response. Measures of leg lean mass may not capture RT-induced adaptation.